Taxonomy, Conservation, and the Future of Native Aquatic Snails in the Hawaiian Islands - Carl C. Christensen; Kenneth A. Hayes; Norine W. Yeung (Diversity, 2021)
Freshwater systems are among the most threatened habitats in the world and the biodiversity inhabiting them is disappearing quickly. The Hawaiian Archipelago has a small but highly endemic and threatened group of freshwater snails, with eight species in three families (Neritidae, Lymnaeidae, and Cochliopidae). Anthropogenically mediated habitat modifications (i.e., changes in land and water use) and invasive species (e.g., Euglandina spp., non-native sciomyzids) are among the biggest threats to freshwater snails in Hawaii. Currently, only three species are protected either federally (U.S. Endangered Species Act; Erinna newcombi) or by Hawaii State legislation (Neritona granosa, and Neripteron vespertinum). Here, we review the taxonomic and conservation status of Hawaii’s freshwater snails and describe historical and contemporary impacts to their habitats. We conclude by recommending some basic actions that are needed immediately to conserve these species. Without a full understanding of these species’ identities, distributions, habitat requirements, and threats, many will not survive the next decade, and we will have irretrievably lost more of the unique books from the evolutionary library of life on Earth.